Produção de codornas europeias e a técnica do ultrassom para analisar o desenvolvimento muscular - Santos, Thailine Santana (2019)
The livestock industry objective to have a precise and objective method to assess the economically important characteristics of the animals while they are still alive and to determine the value of the carcass. Real-time ultrasonography has already been used in large and medium-sized animals, but in quails research are still few. The objective of this study was to evaluate the performance, body development and carcass quality of European quails submitted to diets with different levels of metabolizable energy, as well as the carcass composition using the ultrasound apparatus. Were used 270 European quail (Coturnix coturnix), mixed lot, in the period from 7 to 49 days of age. The birds were housed in cages and distributed in a completely randomized design within three treatments, five replicates and 18 birds per experimental unit. The experimental treatments consisted of three levels of metabolizable energy Phase I- 7 to 21 days old, contend diets energy levels of 2,700; 2,900 and 3100 Kcal/kg and Phase II – 21 to 49 days old, contend diets 2900; 3050 and 3200 kacl/kg of metabolizable energy. Were evalueted the feed intake, weight gain and feed conversion, as well as organ development and carcass quality using the Tukey test at 5% probability. Three ultrasonographies were also performed at 21; 35 and 49 days old, two readings were performed in the ventral portion of the Pectoralis major muscle: a reading was performed in the transverse position of the muscle and another in the longitudinal position, then the birds were slaughtered for organ quantification and body composition. The feed intake was reduced (P <0.05), while the feed conversion improved (P <0.05) with the increase of the energy levels in all phases evaluated. The development of liver was lower (P <0.05), while gizzard increased (P <0.05) with elevation of energy level. At 35 days, the weight of the pancreas, pro-ventricle and gizzard were reduced (P <0.05), while the fat content increased with the highest energy level. At 49 days of age the fat content was higher (P <0.05) at the levels of 2900 and 3100 kcal/kg of metabolizable energy in the diet. A significant effect (P <0.05) was observed to wing yield, but to the other cuts: chest, thigh + overcoat and carcass, there was not the same effect. For sensory analysis, there was no interference of energy levels on the sensory attributes. It was not possible to analyze the fat content by the ultrasound method. However, it was possible to adjust the equation to predict chest area, length and depth, where the area was more representative: Y=0,00242*EM+ 0,20536*Idade- 6,18931, R2 = 81,34%. It is concluded that the increase in the energy level of the feed of 2.700 to 3100 kcal/kg of diets, reduces feed intake and improves the feed conversion of quails, but increases the level of fat in the quails from 35 days of age, without harming the development of the birds as well as the physical and sensorial characteristics of the meat. The in vivo ultrasound technique using to Pectoralis major muscle area by transversal reading, considering to age and energetic level of the diet, lets you predict with major reliability to Pectoralis major size.